Angle specific analysis of hamstrings and quadriceps isokinetic torque identify residual deficits in soccer players following ACL reconstruction: a longitudinal investigation. Issue 8 (18th April 2022) - Read, Paul J.; Trama, Robin; Racinais, Sebastien; McAuliffe, Sean; Klauznicer, Jasenko; Alhammoud, Marine
ABSTRACT: Analysing the isokinetic curve is important following ACL reconstruction as there may be deficits in torque production at specific points throughout the range of motion. We examined isokinetic (60°.s-1) torque-angle characteristics in 27 male soccer players (24.5 ± 3.9 years) at 3 time-points (17 ± 5; 25 ± 6; and 34 ± 7 weeks post-surgery). Extracted data included knee flexor and extensor peak torque, conventional hamstrings: quadriceps (H/Q) ratio, and angle-specific torque using Statistical Parametric Mapping (SPM). There were significant involved limb increases in extension peak torque at each assessment (p<0.001); however, asymmetry favouring the un-involved limb was observed (p<0.01). Flexion peak torque was greater on the un-involved limb at assessments 1 and 2 only (p<0.05). The angle of peak torque was not significantly different at individual time-points or within-limbs across the 3 assessments. SPM revealed involved limb angle-specific reductions in extension torque across the full range of motion at time-points 1 and 2 (p<0.001) but only in angles [51-80°] at assessment 3 (p<0.05). Between limb H/Q angle differences [33-45°] were shown at assessments 2 and 3. The ratio ranged from 1.60-0.74 depending on the angle tested. Angle-specific moment curves are useful for monitoring patterns of strength development during rehabilitation.